The congruence effect between product emotional appeal and country-based emotion: The moderating role of country-of-origin - Felix Septianto; Tung, Moi; Nguyen T. Thai (Elsevier, 2020)
Previous research has suggested that country-based emotions (i.e., emotions associated with a country) can influence consumer evaluations of a product from thatcountry. However, it remains unclear when and how country-based emotions can be influential in consumer decision making. The results from an experiment revealthat only for a destination with a less favorable country-of-origin image will the match (vs. mismatch) between the country-based emotion and the emotional appealof the product advertisement increase the purchase likelihood of the product. Thesefindings are beneficial for local brands in that they can promote tourist spendingat their destination by cooperating with destination marketers in developing integrated promotional campaigns that elicit congruent emotions.